Ifosfamide-induced Encephalopathy in Patients With Uterine Sarcoma - Shih-Hung Tsai (Elsevier, 2010)
Objective: To report two cases of recurrent uterine sarcoma that developed ifosfamide-induced encephalopathy (IIE) with successful management. Case Reports: The patient in the first case developed grade 4 toxicity and had a partial response after the fourth dose of intravenous methylene blue was administered. Full recovery occurred 4 days after the development of IIE. The patient in the second case, who had grade 3 toxicity, had completely recovered 32 hours after the first dose of thiamine. Conclusion: Careful evaluation of patients with recurrent gynecologic cancers and vigilance during infusion of chemotherapeutic regimens are important in reducing the risk and timely management of IIE. Both methylene blue and thiamine appear to be effective treatments for IIE.